Qualitative and quantitive identification of some secondary compounds in the bark of (Salix alba l.) Naturally growing in dohuk by using HPLC . - K. Al-Takay, Talal; C. Al-Daody, Ayad; A. Kasir, Walid (Journal of Kerbala for Agricultural Sciences, 2017)
Separation of some secondary compounds in the bark of Salix alba L. trees was carried out. Sequence extraction with two different polar solvents (Petroleum ether as a non polar solvent and Ethanol 95 % polar solvent) was done using Soxhlet apparatus in order to prepare the crude extract. High performance liquid chromatography (HPLC) was used for chromatographic separation, identification and also determination of some secondary compounds and its percentages. The results were showed a remarkable variation in the kind, number, percentage and the peak area (represented the concentration) of each separated compound. Citric acid, Acetylsalicylic acid and also Cinnamic acid were identified. Acetylsalicylic acid (Aspirin) was isolated for the first time from the bark of Salix alba L. trees .